Inferential based measurement of backlash in servo system. (2021) - Chandrasekar, P.; Srinivasan, K.
Abstract: The presence of backlash in servo system is always deteriorates the controller performance. It resulted in stability problem and poor steady state accuracy. The backlash is proportionate to the wear and tear caused by the friction during continuous movements of the transmission system in machine tool applications. Hence, there is a need to estimate the backlash on a continual basis and this information is fed back to the servo system in order to improve the controller performance. In general backlash error is occurred whenever there is a change in direction of the motor. In this work, the backlash is estimated by measuring backlash distance and this value is displayed in the user interface screen and that value can be added in software to compensate the backlash. The proposed methodology has an online estimation, which eliminates the necessity of physical sensors as compared to the earlier approaches.